Immune dysregulation and dyserythropoiesis in the myelodysplastic syndromes - Alfinito, Fiorella; Sica, Michela; Luciano, Luigiana; Pepa, Roberta Della; Palladino, Carmela; Ferrara, Idalucia; Giani, Umberto; Ruggiero, Giuseppina; Terrazzano, Giuseppe (British journal of haematology, 2010)
Summary The myelodysplastic syndromes (MDS) are clonal disorders characterised by ineffective haematopoiesis with high risk of leukaemia progression. The relevance of immune‐dysregulation for emergence, dominance and progression of dysplastic clones has been suggested, but valuable criteria to obtain insight into these connections are lacking. This study showed significant increase of CD8 lymphocytes and mature B cells in the bone marrow (BM) compared to peripheral blood (PB) of low risk MDS patients. Different BM levels of Regulatory T cells (Treg) identified two sub‐groups in these patients; only the sub‐group with lower Treg percentage showed BM recruitment of CD8 lymphocytes. Different levels of CD54 on BM CD8 cells revealed two sub‐groups of Intermediate‐1 (Int‐1) patients. The sub‐group with higher CD54 expression on BM CD8 showed high levels of this molecule also on CD4 cells. BM recruitment of CD8 lymphocytes in the low risk group and/or the presence of high CD54 expression on BM CD8 in Int‐1 patients were associated with more pronounced dyserythropoiesis and erythropoietin treatment. Our data shed light on the involvement of immune‐mediated mechanisms in Low and Int‐1 risk MDS patients and suggest that BM versus PB levels of immune effectors could represent useful criteria for a more homogeneous grouping of MDS patients.